2022
DOI: 10.1101/2022.05.11.491518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vast heterogeneity in cytoplasmic diffusion rates revealed by nanorheology and Doppelgänger simulations

Abstract: The cytoplasm is a complex, crowded, actively-driven environment whose biophysical characteristics modulate critical cellular processes such as cytoskeletal dynamics, phase separation, and stem-cell fate. Little is known about the variance in these cytoplasmic properties. Here, we employed particle-tracking nano-rheology on genetically encoded multimeric 40-nm nanoparticles (GEMs) to measure diffusion within the cytoplasm of the fission yeast Schizosaccharomyces pombe. We found that the apparent diffusion coef… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 99 publications
(192 reference statements)
1
4
0
Order By: Relevance
“…Similarly high variability has been reported for the diffusion of genetically-encoded nanoparticles expressed in S. pombe (Garner et al, 2023), which is thought to reflect the heterogeneity of the cytoplasmic environment.…”
Section: Viscosity Affects Protein Translation Rate and To A Lesser E...supporting
confidence: 55%
“…Similarly high variability has been reported for the diffusion of genetically-encoded nanoparticles expressed in S. pombe (Garner et al, 2023), which is thought to reflect the heterogeneity of the cytoplasmic environment.…”
Section: Viscosity Affects Protein Translation Rate and To A Lesser E...supporting
confidence: 55%
“…The complex, heterogeneous milieu of the cellular interior has been recently shown to cause heterogeneous diffusion (Garner et al, 2022; Huang et al, 2021; Parry et al, 2014; Śmigiel et al, 2022; Xiang et al, 2020), yet the consequences of such inhomogeneity on compartmentalization and mesoscale molecular dynamics have remained unclear. Through agent-based modeling of diffusion, we have shown that heterogenous viscosity can lead to simulated particle trajectories converging into viscous hotspots, causing the accumulation of diffusing particles into membraneless compartments defined by the higher-viscosity zones.…”
Section: Discussionmentioning
confidence: 99%
“…Such expressways and their associated fluxes may impact reaction kinetics by altering substrate turnover rates, congruent with the model of unusual transport processes potentially modifying reaction kinetics (Bénichou et al, 2010). In the context of subcellular viscous regions (Garner et al, 2022), cells may compensate for geometry-imposed constraints on packing density and size of these regions by altering the viscosity ratio (against the bulk milieu) instead. To map the detailed effects of inhomogeneous viscosity on reaction rates, however, our work suggests that a key prerequisite is to chart a suitable set of metaparameters that provide an adequate description of inhomogeneous diffusion (Jin and Verkman, 2007), as a one-parameter description relying exclusively on the average diffusion coefficient is insufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell components compartmentalize by demixing or preferential interactions in which protein crowders assemble with other biomolecules or membranes. Indeed, diffusion experiments have shown significant spatial heterogeneity in prokaryotes and eukaryotes 8,9 . Crowders captured in large complexes crowd less effectively because a crowder needs to diffuse to generate the depletion force, and complexation reduces the crowder number density.…”
Section: Introductionmentioning
confidence: 99%